The effect of social capital on auditor's performance - Maryamalsadat Mousavi Azghandi; Sahar Jabbari; Hossien Rezaei Ranjbar; Ahmed Al-janabi (Journal of Risk and Financial Management, 2023)
This paper investigates the relationship between social capital and auditor's performance in Iranian listed firms. The sample included 128 firms on the Tehran Stock Exchange from 2014 to 2020. The research method was descriptive-correlational, and the relationship between research variables was explained using regression models based on the panel data. The results illustrated that social capital positively correlates with auditor performance and Audit report quality. In other words, social capital decreases audit opinion shopping, audit expectation gap, internal control weakness, and audit report lag. Therefore, society's influential assets, social capital, and audit report quality strongly influence the auditor's performance. The auditor's performance affects the probability of discovery and reporting material errors and misstatements. Therefore, recognizing influential factors on auditors' performance can improve the quality of audit reports.
Keywords: 650; audit expectation gap; audit opinion shopping; audit performance; audit report lag; audit report quality; internal control weakness; social capital